Safe and probably safe drugs in acute hepatic porphyria - Stölzel, U; Brosche, C; Koszka, C; Stauch, T; Teubner, A; Doss, M O (Cellular and Molecular Biology, 2009)
Acute porphyrias are caused by enzyme defects along the heme synthesis pathway. Patients usually present with abdominal pain, impaired intestinal motility, neurological and psychiatric symptoms, hypertension, tachycardia, hyponatriemia and reddish urine. This article gives an overview over drugs that are recommended in patients with acute hepatic porphyrias and represents a compilation of four so far existing lists.